FIXED POINT THEOREMS FOR NONEXPANSIVE MAPPINGS WITH APPLICATIONS TO GENERALIZED EQUILIBRIUM AND SYSTEM OF NONLINEAR VARIATIONAL INEQUALITIES PROBLEMS - Cho, Y. J.; Petrot, N.; Suantai, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, a method for finding the common element of two nonexpansive mappings are provided. Consequently, we provide some results for the fixed points of an infinite family of nonexpansive mappings and of an infinite family of strict pseudo-contraction mappings. Furthermore, we apply our main result to the problems of finding the solution of generalized equilibrium and system of nonlinear variational inequalities problems. Some interesting remarks will be also pointed out and discussed.